THE EFFECT OF A GUIDED INQUIRY APPROACH TO MEASURING HIGH-LEVEL THINKING SKILLS OF MADRASAH ALIYAH STUDENTS ON ELASTICITY MATERIALS - Rabiatul Adawiyah; Juni Angkowati; Rosy Elfiana; Fatminastiti Fatminastiti (Universitas Lambung Mangkurat, 2021)
Learning activities at MAN 2 Marabahan so far have led to observation activities but have not optimally applied the guided inquiry approach in detail. This resulted in students' higher order thinking skills have not been honed, which is actually very necessary in physics education. This study aims to measure students' higher order thinking skills. This research was analyzed descriptively. The samples of this study were students of class XI IPA 2 and XI IPA 3 as the treatment and class XI IPA 1 as the control class. Based on the results of the study, students' higher order thinking skills were better when using a guided inquiry approach.Keywords: influence, guided inquiry, higher order thinking skills, elasticity AbstrakKegiatan pembelajaran di MAN 2 Marabahan selama ini sudah mengarah kepada kegiatan pengamatan namun belum optimal menerapkan pendekatan inkuiri terbimbing secara terperinci. Hal ini mengakibatkan keterampilan berpikir tingkat tinggi siswa belum terasah, yang sebenarnya sangat diperlukan dalam pendidikan fisika. Penelitian ini bertujuan untuk mengukur keterampilan berpikir tingkat tinggi siswa. Penelitian ini dianalisis secara deskriptif. Sampel penelitian ini adalah siswa kelas XI IPA 2 dan XI IPA 3 sebagai pelakuan dan kelas XI IPA 1 sebagai kelas kontrol. Berdasarkan hasil penelitian keterampilan berpikir tingkat tinggi siswa lebih baik saat menggunakan pendekatan inkuiri terbimbing. Kata kunci: pengaruh, inkuiri terbimbing, keterampilan berpikir tingkat tinggi, elastisitas